STUDI EKSPERIMEN KUAT TEKAN BETON BERDASARKAN URUTAN PENCAMPURAN MATERIAL PENYUSUN BETON DENGAN ADUKAN MANUAL - Asmita, Endra Pramana; Mungok, Crisna Djaya; Handalan, Cek Putra (JeLAST : Jurnal PWK, Laut, Sipil, Tambang, 2015)
The aim of this research where to determine the effect of mixing the precursor material is done manually to slump, the characteristic concrete compressive strength, tensile strength and modulus of elasticity of concrete sides. Testing includes compressive strength, tensile strength and modulus of elasticity sides. Determination of concrete mix using methods ACI modification. The planned concrete quality is fc '= 22.5 MPa. The experimental results obtained sequence of mixing cement, sand, water, crushed stone which produces most compressive strength characteristics compared with other mixing sequences with an average of 29.124 MPa. For a split tensile strength values ​​obtained sequence of mixing sand, cement, crushed stone, water and the order of mixing cement, sand, water, crushed stone produce the most divisive tensile strength compared with other mixing sequences with an average of 2.978 MPa. As for the value obtained sequence modulu elasticity mixing cement, sand, crushed stone, water produces elastic modulus of the most good with an average of 34336,023 MPa.   Keywords: Mixing sequence, time, Compressive Strength, Pull Shopping